Oxidative synthesis of yellow photoluminescent carbon nanoribbons from carbon black. (15th October 2021) - Khodabakhshi, Saeed; Fulvio, Pasquale F.; Sousaraei, Ahmad; Kiani, Sajad; Niu, Yubiao; Palmer, Richard E.; Kuo, Winson C.H.; Rudd, Jennifer; Barron, Andrew R.; Andreoli, Enrico
Abstract: Micrometer long multilayer carbon nanoribbons with high oxygen content and nitrogen doping were obtained from the nitric acid treatment of Black Pearls 2000. The nanoribbons (NRs) exhibited yellow light emission under UV excitation. The oxidation of other grades of carbon black yielded irregular and small graphene oxide fragments or carbon quantum dots instead. Remarkably, the familiar and straightforward treatment of carbon materials with nitric acid reemerges as a powerful tool for the synthesis of technology-relevant carbon nanoribbons, and unlocking the potential of such straighforward oxidation chemistry applied to inexpensive and commercially available carbon black. Graphical abstract: Image 1 Highlights: Carbon nanoribbons are uniquely obtained from oxidation of carbon black (CB) BP2000. Oxidation of Vulcan, Monarch and Acetylene Black grades yield graphene oxide sheets and carbon dots. Nanostructure depends on CB surface area, amount of amorphous carbon and size of basic structural units. Nanoribbons have yellow emission modulated by nitrogen doping and to oxygen defects.